An updated review on the neuropsychological profile of subjects with bipolar disorder - Szmulewicz, Alejandro G. (2015)
Background: In recent years, growing interest in the neuropsychology of bipolar disorder has emerged, giving rise to the accumulation of a robust body of evidence on this topic and to several related questions. Objective: To provide a state-of-the-art overview of the neuropsychological profile of bipolar disorder. Method: A thorough literature search was performed. Published research evidence was summarized and organized along three key pathways: findings from cross-sectional studies of cognition in bipolar patients, cognitive heterogeneity among affected subjects, and trajectory of neuropsychological deficits. Results: At least two thirds of bipolar patients display neuropsychological deficits, even in euthymia. Although bipolar disorder was found to be associated with an increased risk of dementia, data from elderly subjects and longitudinal research do not support a worsening of cognitive performance over time. Discussion: Cognitive dysfunctions are part of the clinical conceptualization of bipolar illness. However, they may not be present in all affected subjects and their course appears to be stable in most cases. Available evidence may be highlighting the fact that bipolar disorder is characterized by remarkable heterogeneity regarding cognitive outcomes. Different variables may be related to such heterogeneity and should be the focus of therapeutic approaches and further research.